Differentiation of Atrial Cardiomyocytes from Pluripotent Stem Cells Using the BMP Antagonist Grem2 - Bylund, Jeffery B. (J Vis Exp, 2016)
Protocols for generating populations of cardiomyocytes from pluripotent stem cells have been developed, but these generally yield cells of mixed phenotypes. Researchers interested in pursuing studies involving specific myocyte subtypes require a more directed differentiation approach. By treating mouse embryonic stem (ES) cells with Grem2, a secreted BMP antagonist that is necessary for atrial chamber formation in vivo, a large number of cardiac cells with an atrial phenotype can be generated. Use of the engineered Myh6-DSRed-Nuc pluripotent stem cell line allows for identification, selection, and purification of cardiomyocytes. In this protocol embryoid bodies are generated from Myh6-DSRed-Nuc cells using the hanging drop method and kept in suspension until differentiation day 4 (d4). At d4 cells are treated with Grem2 and plated onto gelatin coated plates. Between d8-d10 large contracting areas are observed in the cultures and continue to expand and mature through d14. Molecular, histological and electrophysiogical analyses indicate cells in Grem2-treated cells acquire atrial-like characteristics providing an in vitro model to study the biology of atrial cardiomyocytes and their response to various pharmacological agents.